Mosby's dictionary of medicine, nursing & health professions. (St Louis, Missouri, 2013)
This dictionary offers complete definitions of current health care, including disorders, procedures, and drugs. It contains 2.300 full-color illustrations, nearly 5.000 new terms, 74 appendixes, and a color atlas of human anatomy
Keywords: Nursing,Điều dưỡng; Dictionaries,Từ điển